Pelatihan Peningkatan Penerapan Standar Operasional Prosedur (SOP) Dalam Meningkatkan Layanan Akademik - Almurni, Siti; Mustika, Maya; Mais, Rimi Gusliana; Nafisah, Siti; Anthonino, Dean Salomo; Maronrong, Ridwan (Bagian Pengelolaan Jurnal dan Penerbitan - Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta (BPJP - STEI), 2024)
The purpose of carrying out this activity is to answer the needs of educators at Universidade Dilli, Timor Leste to learn and apprentice on the implementation of the standard operating procedures for Study Program Education, Research and Community Service at STIE Indonesia Jakarta. The target of this activity is the teaching staff of Universidade Dilli, Timor Leste to understand and increase their knowledge related to the SOP implemented at STIE Indonesia Jakarta with the hope of becoming an understanding for improving the SOP implemented by Universidade Dilli, Timor Leste. The method of carrying out this activity is a detailed explanation of the running system, SOP training and a 10-day internship which is held offline in the YPFJ Room, Indonesian College of Economics, Jakarta, East Jakarta on the SOP for Implementation of Research, Community Service and Education (PRODI) STIE campus Indonesian Jakarta. This socialization provides awareness to teaching staff, so that it can improve the performance of teaching staff at Universidade Dilli, Timor Leste.